A survey on the status of Filipiniana rare books in selected institutions in Metro Manila - Siapno, Joanna O.; Faderon, Rosalie B.; Tarlit, Rodolfo Y.; Rey, Emma M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
Filipiniana rare books (FRBs) are valuable and priceless sources of Philippine cultural heritage. These are books published from 1523 to 1945 but some out-of-print books beyond the time frame are considered rare. Rare book librarianship is one branch of librarianship that needs further study in the country.
The study included nine institutions in Metro Manila. These are the Ateneo de Manila University Rizal Library (ADMU), De La Salle University Library (DLSU), Filipinas Heritage Library (FHL), Lopez Memorial Museum Library (LMM), Ortigas Foundation Library (OFL), The National Library (TNL), University of the Philippines Diliman Main Library (UPD), University of Santo Tomas Miguel de Benavides Library (UST), and UP Jorge B. Vargas Museum and Filipiniana Research Center Library (VM).
This study, focused entirely on Filipiniana rare books, aimed to determine the strength of each institution's collections in terms of subject and period coverage, their policies and practices concerning Filipiniana rare book collections, issues and concerns regarding Filipiniana rare book collections and the implications of these practices, and the issues and concerns towards the development and training of rare book librarians.
The study used the descriptive research method to find out the general picture of the status of these collections. Data were gathered through the completion of the comprehensive survey questionnaire, ocular inspection, series of interviews with the respondents' representatives (librarians-in-charge), and analysis of documents such as their opening manuals, policies and available bibliographies.
The FRB collections cover various subjects but are predominantly about religion, history of the Philippines and its various provinces and languages. There was also a gradual increase in terms of period coverage especially in the latter half of the 19th century. The different aspects of rare book librarianship tackled are collection development, cataloging and classification, conversation and preservation, reference and access, security, promotion and staff. Although there are some differences between and among the institutions, certain practices stand out showing uniformity in rare book librarianship in the country.
Differences exist among the number of rare books staff in each institution as well as in their qualifications and experiences which then result in varying practices implemented on FRBs. It is recommended that formal training be undertaken by rare book librarians through the inclusion of some courses relating to rare books in the library and information science curriculum. The staff should also have continuous training on rare book management.
The study also developed the Union Catalog of Filipiniana Rare Books, 1523-1900, a union catalog union of the collections of the nine institutions based on the bibliographical lists provided by the respondents. It has a total of 4,944 title entries in different foreign languages and local dialects with duplicate titles available in the various institutions. It is arranged chronologically according to year of publication and alphabetically for entries in the same year.
Vita.
"April 2010."
Special Problem (Master of Library and Information Science)
Keywords: Catalogs, Union -- Philippines -- Manila Metropolitan Area; Libraries -- Special collections -- Rare books